EFEK WAKTU MILLING TERHADAP SIFAT MAGNET KOMPOSIT Ni-C - -, Yunasfi (National Standardization Agency of Indonesia, 2013)
EFFECTS OF MILLING TIME ON MAGNETIC PROPERTIES OF Ni-C COMPOSITES. A study on the effect of milling time to magnetic properties of Ni-C composites has been carried out. The composite materials of Ni-C was prepared by mixing nickel and carbon (C) powders with the weight ratio of Ni and C is 2% : 98%, and by varying the milling time for 25, 50 and 75 hours using High Energy Milling (HEM) technique. Results of identification by X-ray diffractometer (XRD) showed that X-ray diffraction peak intensity decreased and particle size was going smaller with the increasing of milling time. Whereas the optimal milling time for Ni-C composite system is 50 hours. This is indicated by the largest surface area (about 483 m2/g) and highest magnetic properties of Ni-C compared with other milling time. The results of magnetic parameter value for milling time of 50 hours shows the highest values of Ms (Saturated Magnetization), Mr (Remanence Magnetization) and Hc (Coercive Field) i.e. 2.29 emu/g, 0.43 emu/g and 0.017 Tesla, respectively. The highest value of magnetoresistance ratio (MR) i.e. 14.22% at 7.5 kOe magnetic field was also reached. Keywords : Ni-C Composites, Milling Technique, Magnetic Parameters, Magnetoresistance Ratio.